Data supporting "A novel cold wire gas metal arc (CW-GMA) process for high productivity additive manufacturing" - Wang, Chong; Wang, Jun; Bento, João; Ding, Jialuo; Rodrigues Pardal, Goncalo; Chen, Guangyu; Qin, Jian; Suder, Wojciech; Williams, Stewart W. (Cranfield University, 2023)
This is a supplementary figure, showing the experimental setup for building the large-scale component with the CW-GMA process: (a) experiment setup, and (b) monitors for thermal camera and process camera.
Keywords: 'Wire arc additive manufacturing'; 'CW-GMA'; 'High deposition rate'